Investigating Microglia Phenotype at the Chronic Stage of Ischemic Stroke After Gene Therapy with AAV-NeuroD1 - Naomi Hawreluk (Inquiry@Queen's Undergraduate Research Conference Proceedings, 2026)
Ischemic stroke remains a leading contributor to mortality and long-term neurological disability worldwide. While improvements in emergency care have increased survival rates, most effective clinical interventions are largely restricted to the acute phase of injury. As a result, increasing attention has shifted toward understanding cellular processes that influence tissue remodelling and recovery during the chronic stage. Microglia, the resident immune cells of the central nervous system, play a critical role in shaping recovery outcomes, yet their behaviour during the chronic stage of stroke remains poorly defined. An increasingly compelling area of research has investigated regenerative gene therapies. One such therapy involves adeno-associated virus (AAV) mediated delivery of the transcription factor NeuroD1, which has demonstrated robust neuroregenerative effects in both rodent and non-human primate models of ischemic stroke, including increased neuronal density and reduced gliosis. Despite these promising outcomes, the impact of NeuroD1 treatment on microglial populations during the chronic stage of stroke is not well understood. The present study investigates microglial distribution and phenotype in chronic-stage ischemic stroke tissue following AAV-NeuroD1 gene therapy in non-human primates. Brain tissue collected nine months after transient middle cerebral artery occlusion was immunolabeled for Iba1 to identify microglia and counterstained with DAPI to label nuclei. Quantitative image analysis was performed to assess microglial density and spatial distribution in ipsilateral, stroke-affected regions compared to contralateral control regions, as well as across control, low-titer, and high-titer NeuroD1 treatment groups. By examining microglial patterns in chronically injured tissue, this study provides foundational insight into how regenerative gene therapy may influence the long-term neuroimmune environment after stroke.